Labial vibrants in Mangbetu - Olson, Kenneth S.; Mbiri Koogibho, David (AAeO - Afrikanistik-Aegyptologie-Online, 2013)
This paper presents a digital list of words and short phrases that include labial vibrants (i.e. trills and flaps) in Mangbetu (D. R. Congo). The wordlist includes orthographic and broad phonetic transcriptions of each item, French and English glosses, MP3 and WAV recordings of each item, and metadata for resource discovery. An archival form of the list was deposited into an institutional archive (the Speech and Language Data Repository) which includes a WAV digital recording of the entire session, de-scriptive markup encoding of the list in XML employing Unicode transcription, and a metadata record. The presentation form was generated from the archival form.